Chemotherapy-Induced Cognitive Impairment and Neuroaxonal Damage: Investigating the Role of Serum Neurofilament Light Chain - Husni Minanda Fikri; Syafrita, Yuliarni; Lydia Susanti; Syarif Indra; Restu Susanti; Reno Bestari (HM Publisher, 2025)
Background: Chemotherapy-induced cognitive impairment (CICI), colloquially termed